2002
DOI: 10.2214/ajr.179.1.1790179
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging of Mucinous Carcinoma of the Breast

Abstract: The MR imaging findings in mucinous carcinomas include dynamic curves of the gradually enhancing type and a very high signal intensity on T2-weighted images compared with other histologic types of invasive ductal carcinoma. These findings appear to be useful for diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0
6

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 8 publications
4
47
0
6
Order By: Relevance
“…Kawashima and colleagues have reported high signal intensity on T2-weighted images and gradual enhancement pattern on dynamic MR imaging to be speciˆcˆndings of MU of the breast. 29 We suppose that high ADC may be an additional speciˆcˆnding for diagnosing MU. Compared to other cancers andˆbroadenoma, MU demonstrated lower cell density and higher extracellular water content, which re‰ected a mucin pool.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kawashima and colleagues have reported high signal intensity on T2-weighted images and gradual enhancement pattern on dynamic MR imaging to be speciˆcˆndings of MU of the breast. 29 We suppose that high ADC may be an additional speciˆcˆnding for diagnosing MU. Compared to other cancers andˆbroadenoma, MU demonstrated lower cell density and higher extracellular water content, which re‰ected a mucin pool.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is limited because it includes only 4 cases of MU because MU is rare and comprises only one to 4z of primary breast malignancies. 29 Further study will be needed to clarify details.…”
Section: Discussionmentioning
confidence: 99%
“…Mucinous carcinoma typically shows gradual enhancement on dynamic contrast enhancement study. 12 In invasive ductal carcinoma with massive necrotic tumors or other metaplastic carcinomas, internal components with high signal intensity on T 2 images correspond to necrosis, cysts, or chondroid matrix and do not enhance in contrast study. Yuen's group reported that nonmucinous carcinomas with strong high signal intensity on T 2 -weighted images frequently showed washout phenomenon and rim enhancement, but there were no cases withˆbrous capsule showing expanding growth pattern.…”
Section: Discussionmentioning
confidence: 94%
“…Various studies suggest that high signal intensities in lesions on T2-w MRI cannot differentiate benign and malignant lesions [6,60,61,62,63,64,65,66]. However, numerous other studies indicate that the high signal intensity in lesions on T2-w MRI is distinctive in the discrimination between benign and malignant lesions [67,68,69,70,71,72]. Few other studies conclude that T2-w features are promising diagnostic features for the classification of benign and malignant lesions [73,74,75].…”
Section: Breast Mri Databasementioning
confidence: 99%